INTEGRASI NILAI-NILAI AL-QURAN DAN HADITS DALAM KURIKULUM PEMBELAJARAN BAGI PESERTA DIDIK MADRASAH TSANAWIYAH AL MUHAMMAD CEPU - Zainal Muttaqin, Faiz; Anwar, Ahmad; Sariman, Sariman; Almurtaqi, Moch Ridwan (Al Fattah Ejournal Sma Al Muhammad Cepu, 2024)
Teaching Al-Quran Hadith includes teachings about faith in Allah and how daily actions reflect integrity in the student environment. It also covers how one shows love for the Koran, and various other aspects. This research uses a descriptive qualitative method, where the data analyzed is in the form of symptoms or other forms that can be categorized such as words, images or documents during the research process. Data collection techniques used include interviews and documentation. Data analysis was carried out through several stages, namely data reduction, data presentation, and drawing conclusions. The results of this research are: This integration is also reflected in the students' proficiency in reading the Al-Quran, where almost all students are able to read the holy verses of the Al-Quran. This success is supported by school programs that strengthen their understanding, as well as the An-Nadhiyah program in the environment where MTs Al Muhammad Cepu students live. Integration is also found in the way they greet, smile and are polite towards others and older people, as well as diligently studying the Koran and Hadith